Spirituality and religiosity as predictors of subjective wellbeing in older Mexican adults - González-González, Alejandro; Andrade Palos, Patricia; García-Chanes, Rosa Estela; Sánchez Hernández, María Enriqueta; Betancourt Ocampo, Diana (Frontiers in Psychology, 2025)
ObjectiveThis study analyzed the effect of spirituality and religiosity on subjective wellbeing in Mexican older adults, controlling some sociodemographic variables (e.g., sex, age, schooling, who they live with, monthly income) and health variables (e.g., health perception, difficulties in carrying out activities, presence of medical conditions, depression).MethodsA non-probabilistic sample of 923 older adults (x¯= 74.49, SD = 7.46) was obtained, 74.8% were women and 25.2% men. The EBS-8 subjective wellbeing scale was used to assess the dependent variable. To assess religiosity, the Religious Involvement dimension of ASPIRES was, and to assess spirituality it was used the dimension of Importance of Spiritual Beliefs of the Spiritual Questionnaire, both dimensions in their Spanish-adapted versions. Was used a questionnaire with 16 closed-option questions which evaluate self-perception of health, self-reported difficulty in performing activities of daily living and the presence of medical conditions. The scale adapted to the Mexican population of the Yesavage Geriatric Depression Scale (GDS) was used.ResultsThe results showed that spirituality and living with a partner have positive and significant effects on subjective wellbeing, while depression and difficulties in performing activities of daily living reduce it, this regression model explained 17% of the variability in subjective wellbeing.ConclusionIn the present study, it was observed that in each of the models tested, spirituality played an important role as a predictor of subjective wellbeing, and even remained stable when demographic (sex, age, schooling, who they live with) and health (health perception, difficulties in carrying out activities, depression) variables were included.